Implementasi Pendidikan Ekonomi Syariah di SMP Alam Azzahra Way Jepara - Kurniasih, Apri; Hastuti, Nur (EKSYDA: Jurnal Studi Ekonomi Syariah, 2024)
The purpose of this article is to describe the implementation of sharia economic education at SMP Alam Azzahra Way Jepara. The research was conducted using a qualitative phenomenological type approach. Findings in the research include: 1) Implementation of sharia economic education is carried out through implementing business learning as one of the school curriculum contents; 2) sharia economic education is carried out using a profit sharing approach; and 3) the form of muhdarabah carried out at the school includes the type of mudharobah muqayyadah.